2015
DOI: 10.1103/physreva.92.053814
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of qubit ensembles under optimizedπ-pulse driving

Abstract: We propose technique of simultaneous excitation of disordered qubits providing an effective suppression of inhomogeneous broadening in their spectral density. The technique is based on applying of optimally chosen π-pulse with non-rectangular smooth shape. We study excitation dynamics of an off-resonant qubit subjected to strong classical electromagnetic driving field with the fast reference frequency and slow envelope. Within this solution we optimize the envelope to achieve a preassigned accuracy in qubit sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…( 3) [47]. For a system with inhomogeneous broadening, for example, doped rare-earth ions in crystals, the π-pulses should be implemented in a more sophisticated way [48]. The influence of inhomogeneous broadening and dephasing on phase coherence has been studied in other contexts [49] while the effect on the SPP emission may be minor because SPP modes already have broad bandwidth in the range of THz.…”
Section: Evolution Of Intermediate States-now We Turn To the Intermed...mentioning
confidence: 99%
“…( 3) [47]. For a system with inhomogeneous broadening, for example, doped rare-earth ions in crystals, the π-pulses should be implemented in a more sophisticated way [48]. The influence of inhomogeneous broadening and dephasing on phase coherence has been studied in other contexts [49] while the effect on the SPP emission may be minor because SPP modes already have broad bandwidth in the range of THz.…”
Section: Evolution Of Intermediate States-now We Turn To the Intermed...mentioning
confidence: 99%
“…Note that by using an interplay between different Fourier components of the external electromagnetic signal, one can also achieve a synchronization of a qubit ensemble [34] despite of the unavoidable disorder in excitation energies of Josephson qubits [35].…”
Section: Toy Modelmentioning
confidence: 99%
“…In Ref. [42] a generalized non-rectangular envelope of π-pulse was proposed. This π-pulse allows to compensate the effects of disorder in frequencies in a non-interacting qubit system.…”
Section: Modelmentioning
confidence: 99%
“…For non-interacting qubits a suppression of an inhomogeneous broadening was demonstrated for the nitrogenvacancies in diamonds [39][40][41]. We later proposed an optimized shape of the driving pulses for the broadening suppression and studied the effect of strong driving on an entanglement in the hybrid qubit-cavity system [42,43]. In the context of disordered interacting qubits it was shown that an external driving can enhance the localization effects, namely, a driven transition to the dynamical MBL phase was discovered for an engineered Floquet Hamiltonian [44].…”
Section: Introductionmentioning
confidence: 99%